LITERATURE AND EVIL : Dostoyevsky's Poetic Thinking On Evil - Adian, Donny Gahral (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2008)
Philosophical and theological reflections claim evil as thebinary opposite of the good. This way of thinking cannotunderstand the evil of terror. To understand the nature of evilwe need a poetic way of thinking. A poetic way of thinking goesbeyond the binary of good and evil. Dostoyevsky locates evilwithin us contingent and finite human beings. Only byacknowledging this we can gain freedom to act and create.